Numerical analysis of time-dependent behavior of an embankment on PVD-installed Sebou soft soils - Mridakh, A. H.; Nguyen, B. P.; Ejjaaouani, H.; Labied, H. (Frontiers in Built Environment, 2025)
In this paper, finite element (FE) modeling is conducted for a high-speed railway embankment on soft soils in Sebou, Morocco. Discrepancies arise between predicted and measured behaviors when using standard creep models. To address this, an advanced anisotropic creep constitutive model, known as Creep-SCLAY1S, is applied for comparison, focusing on the prefabricated vertical drain (PVD) treated soft soils. This advanced model incorporates fabric anisotropy, soil structure, and time-dependent behavior. The time-dependent soft soil creep model (SSCM) is also employed for further comparison. Numerical predictions are then compared with field instrumentation data. Results indicate that Creep-SCLAY1S offers improved predictions of in situ measurements, particularly post-construction, and provides a more accurate peak excess pore pressure during the embankment’s rapid surcharge phase.